Dynamic interactions between soil cadmium and zinc affect cadmium phytoavailability to rice and wheat: Regional investigation and risk modeling. (December 2020) - Yang, Yang; Li, Yanling; Chen, Weiping; Wang, Meie; Wang, Tianqi; Dai, Yating
Abstract: Characterizing the interactions between Cd and Zn with respect to the soil soluble Cd and crop Cd uptake allows the development of risk-based approaches to the performance of grain crops. By means of a three-year survey of 358 rice fields and 206 wheat fields across China, this study investigated the effect of Cd–Zn interactions on the phytoavailability of Cd to rice and wheat. The interactive nature between the Cd:Zn ratio and pH of soil affected crop Cd uptake, and the resulting grain Cd intake risk, were examined by the Free-Ion Activity-based model and probability analysis. In highly acidic rice soils (pH < 5.9), soil Zn had no effect on rice Cd uptake, whereas, under near-neutral conditions (pH > 5.9), a site-specific influence of soil Zn on grain Cd concentration was found. Soil Zn could inhibit Cd uptake and translocation by the plant in soil-wheat system when the soil Cd:Zn ratio decreased to 0.0083 and lower. Rice grain poses a significant health risk to local consumers due to its high Cd accumulation and its low Zn accumulation. In order to reduce the health risks from dietary Cd to local consumers, approximately 63.9% of the rice fields and 30.5% of the wheat fields require strategies ameliorating soil acidity in rice soils and increasing Zn concentrations in wheat soils. Graphical abstract: Image 1 Highlights: Interaction between Cd and Zn in acidic rice soils appears to be an anomaly. Adding additional Zn to wheat soils is effective in inhibiting Cd uptake by wheat. Zinc-fertilizer treatment is not advisable for rice cultivation in soils rich in Zn. Probability analysis provides an effective risk-based approach for safer crop practice. Abstract : Abstract capsule: Cadmium and Zn would interact dynamically, according to soil's Cd:Zn ratio and pH, to change the chemistry of soil Cd, and consequently to influence the rice and wheat Cd uptake.